1980
DOI: 10.1002/1097-0142(19800801)46:3<508::aid-cncr2820460315>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy (2500 rad) for testicular leukemia: Local control and subsequent clinical events: A southwest oncology group study

Abstract: The effectiveness of radiotherapy, 2500 rad over two weeks, in treating leukemic infiltrates of the testicles was studied in 38 boys who met the requirements for tissue conformation of testicular involvement and examination of the bone marrow. The study group was heterogeneous with respect to specific histology and prior therapy. Complete regression of testicular infiltrates was confirmed by repeated biopsy examinations of 32 of 33 patients undergoing the procedure. The single treatment failure occurred in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

1981
1981
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 10 publications
1
13
0
1
Order By: Relevance
“…Five of seven patients with early ITR in this study had subsequent hematological relapse and died. Similar results have been reported in other studies [2,4,6,7,13,14,32]. Consequently, in our opinion, for these patients, pilot studies with new modalities of intensive therapy should be made, followed, where possible, by marrow transplant.…”
Section: Disc Usslo Nsupporting
confidence: 89%
See 1 more Smart Citation
“…Five of seven patients with early ITR in this study had subsequent hematological relapse and died. Similar results have been reported in other studies [2,4,6,7,13,14,32]. Consequently, in our opinion, for these patients, pilot studies with new modalities of intensive therapy should be made, followed, where possible, by marrow transplant.…”
Section: Disc Usslo Nsupporting
confidence: 89%
“…The review of the reported studies [19,20,23,31] shows that the overall rate of subsequent marrow or CNS relapses for patients with positive biopsies was 50% (21 out of 42 patients), which was significantly higher than the 16% (38 out of 229) for patients with negative biopsies. Consequently, we think that the practice of routine testes biopsy, employing new techniques with cell markers [32], maintains its value in detecting residual disease, at least until more effective therapies show that incidence of occult infiltrates is irrelevant. In our experience, combined local and moderately intensified systemic treatment is effective in most cases with occult testicular infiltrates.…”
Section: Disc Usslo Nmentioning
confidence: 99%
“…Testicular relapse usually occurs within the first months off therapy, which suggests that leukemic infiltration of the testes may have been present when therapy was stopped. Once testicular relapse occurs, the majority of patients will relapse in other sites [40]. Studies of prophylactic testicular irradiation given after remission induction have not shown significant benefit in preventing testicular relapse [41].…”
Section: Discussionmentioning
confidence: 99%
“…In the pediatric population testicular relapse is more common in children who, at the time of initial diagnosis, have a high WBC [2,3,7,8,11,14,21,23], splenomegaly and/or hepatomegaly [2,14,21], markedly enlarged lymph nodes [9,21], a mediastinal mass [2,21], and lymphoblasts of T-cell lineage [3]. It seems that these patients who develop a testicular relapse have a disease more like that of lymphoma [2].…”
Section: Discussionmentioning
confidence: 99%
“…Today, the treatment of choice is radiation, 2,500 cGy delivered in ten fractions, with systemic chemotherapy [5,8,10,11,211. Both testes are included in the treatment field because of the high incidence of occult involvement in the clinically normal, contralateral testicle [7]. Complete regression can be achieved in 1-6 months [8].…”
Section: Case Reportmentioning
confidence: 99%